STRATEGI KOMUNIKASI PERUBAHAN PERILAKU DALAM PENDIDIKAN KESEHATAN DI TK‘AISYIYAH BUSTANUL ATHFAL KOTA BENGKULU - Hidayati Hidayati; Nunung Nursyarofah; Yuli Dwi Setyowati; Ganesa Deltasari; Fauziah Alam (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2021)
Health education is the main element in early childhood education. Several government policies have also integrate health education into Early Childhood curriculum Education, however, its implementation has not been realized in all early childhood institutions. TK ‘Aisyiyah Bustanul Athfal (TK ABA), is the oldest PAUD institution in Indonesia. Along the way, he continues to improve to improve the quality of learning both from the curriculum and the quality of educators (teachers). This article is an evaluation of education and training activities carried out by DIKDASMEN PP Aisyiyah in collaboration with UHAMKA in Bengkulu city which is a series of training in eight provinces throughout Indonesia. This evaluation is to assess health education materials through a behavior change communication approach. The method used is conducting pretest and posttest as well as in-depth interviews with 3 training participants. The results of the posttest showed an increase in knowledge of early childhood teachers after the training was carried out. All informants said the importance of health education in the Early Childhood Education curriculum.